Sophocles' Antigone : a new translation - Sophocles (Cambridge University Press, 2011)
Sophocles' Antigone comes alive in this new translation that will be useful for academic study and stage production. Diane Rayor's accurate yet accessible translation reflects the play's inherent theatricality. She provides an analytical introduction and comprehensive notes, and the edition includes an essay by director Karen Libman. Antigone begins after Oedipus and Jocasta's sons have killed each other in battle over the kingship. The new king, Kreon, decrees that the brother who attacked with a foreign army remain unburied and promises death to anyone who defies him. The play centers on Antigone's refusal to obey Kreon's law and Kreon's refusal to allow her brother's burial. Each acts on principle colored by gender, personality and family history. Antigone poses a conflict between passionate characters whose extreme stances leave no room for compromise. The highly charged struggle between the individual and the state has powerful implications for ethical and political situations today.